Respostas

2014-03-30T16:16:40-03:00
2014-03-30T16:19:51-03:00
(3x²-5x+2)+(x²+6x-4)+ (5x -7) = 0 

3x² -5x +2 +x² +6x -4 +5x -7 = 0

4x² -5
x +2 +6x -4 +5x -7 = 0

4x² +6x -4 +2 -7 = 0

4x² +6x -9 = 0

Δ = b² - 4.a.c 
Δ = 6² - 4. 4. (-9)
Δ= 36 + 144
Δ= 180


X= -b +/- 
√Δ
        2.a

X = -6 +/- 
√180  
            2.4

X'= -6 + 13,4            X''= -6 - 13,4  
         8                               8

X'= 7,4                    X''= -19,4  
      8                               8

X'= 1,85                   X''= 2,425

Prontoo, qualquer dívida é só perguntar! Pode dar um obrigado e escolher como a melhor resposta? Beijoos